A questionnaire-based study to assess the awareness about package inserts amongst the resident doctors in a medical college of North India - Kahkashan, Iram; Farooq, Majid; Imran, Semira (International Journal of Basic & Clinical Pharmacology, 2022)
Background: A package insert (PI) is a document certified by the administering licensing authority, provided along the package of a drug. They are a valuable source of knowledge and can be of tremendous help to doctors as doctors are evidence based. The objective of this study was to assess the awareness about package inserts among residents in a teaching hospital in north India. Methods: The present study was a cross-sectional, observational study carried out on residents in SKIMS Medical College, Srinagar (Jammu and Kashmir) to assess the awareness of participants regarding PIs. The questionnaire was pre-validated and then was used to elicit responses from the residents about their knowledge and opinion regarding the PIs. Results: A total of 96 residents participated in the study. About 67.7% of the participants agreed that PIs augment drug information but only 47.9% of the residents referred PIs as a source of knowledge for indication/contraindication/ adverse effects. 57.29% asserted it is important to tell the patient to read the package insert. Unfortunately, only 8.3% of the study participants had the knowledge of DRUG ACTS governing the information to be provided on PIs in India. Conclusions: The present study revealed that the residents have good attitude and knowledge towards PIs. However, the information provided on Package Inserts was not optimally used by them. The results of this study strongly suggest that there is a need to create awareness among resident doctors about PIs.